PERLINDUNGAN HUKUM HAK DESAIN INDUSTRI KEKAYAAN INTELEKTUAL TERHADAP PENGRAJIN SONGKET BALI DI KLUNGKUNG, SEMARAPURA - Adnantara, Kadek Frediandrika (Jurnal Yustitia, 2024)
Intellectual property protection is to provide legal protection for the ownership of public and private intellectual property rights, which is the basis of the development of the creative economy and makes an important contribution to the development of the country. As a developing country, Indonesia must be able to take appropriate steps to anticipate all changes and developments as well as global trends in order to achieve national goals. The purpose of this study is to determine the protection of Intellectual Property Rights for Songket Fabric Industrial Rights in Klungkung Village Bali and to find out the Registration of Intellectual Property Rights for Songket Fabric Industrial Rights The research method used is legally empirical, namely through the use of laws in terms of norms or Dassault Symphony and social reality, cultural, or Dassian. The results showed that Balinese songket cloth can obtain Intellectual Property Rights, especially Industrial Design Rights.